Taking it Big : C. Wright Mills and the Making of Political Intellectuals - Aronowitz, Stanley (Columbia University Press, 2012)
Charles Wright Mills (1916-1962) was a pathbreaking intellectual who transformed the independent American left in the 1940s and 1950s. Often challenging the established ideologies and approaches of fellow leftist thinkers, Mills was central to creating and developing the idea of the "public intellectual" in postwar America and laid the political foundations for the rise of the New Left in the 1960s. Written by Stanley Aronowitz, a leading sociologist and critic of American culture and history, "Taking it Big" reconstructs the making of this icon and the new dimension of American politics.